The Mechanical Behavior of Salt X : Proceedings of the 10th Conference on the Mechanical Behavior of Salt (saltmech X), Utrecht, the Netherlands, 06-08 July 2022. - de Bresser, J. H. P.; Drury, M. R.; Fokker, P. A.; Gazzani, M.; Hangx, S. J. T.; Niemeijer, A. R.; Spiers, C. J. (Milton : Taylor & Francis Group, 2022)
The Mechanical Behavior of Salt X will appeal to graduate students, academics, engineers and professionals working in the fields of salt mechanics, salt mining and geological storage of energy and wastes, but also to researchers in rock physics in general.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books